Pengembangan Kawasan Tanah Lemo Dan Ara Sebagai Pusat Industri Kerajinan Miniatur Kapal Phinisi Di Kecamatan Bontobahari Kabupaten Bulukumba - Baharuddin - Baharuddin; Lukman Bochari; M. Rizal Firmansyah (Faculty of Engineering UNHAS, 2019)
The Tanah Lemo and Ara village area are located in Bonto Bahari District, Bulukumba Regency. This area is very possible to develop into the center of the Phinisi ship miniature manufacturing industry, considering that the land of Bulukumba is known to have a historical value that is strongly attached to the culture of panrita lopi (expert boat maker). The most famous potential in the District of Bonto Bahari is the Phinisi Shipbuilding industry. The phinisi ship industrial area in Bonto bahari district is currently located in Tanah Lemo Sub-District. Because of the proficiency of the Tanah Lemo community in making phinisi ship from generation to generation. Aside from being an effort to preserve culture, this miniature phinisi ship business commodity has bcome an economic potential due to increase the number of tourist visits which quite significant in recent years to Bulukumba district. The location of Lemo can be developed as the center of the Phinisi Ship Miniature industry in the District of Bonto Bahari, Bulukumba Regency. This problem seen with the condition of the coastal area and the manufacture of miniature ships that are still in the same condition, while there are other potentials that can support the development of Phinisi ship building, so that in the future this area can be more developed, development direction is needed. The results of the discussion for the future are the development of facilities and infrastructure, especially the road network as access from the Phinisi Shipbuilding site and towards Lemo-Lemo beach, development in the capture fisheries sector to help support the economy of the Tanah Lemo coastal area, development of the Phinisi Shipbuilding area, tourism development natural beach Lemo - Lemo. Promoting the potential of natural resources owned by the Tanah Lemo beach area, so that in the future the Tanah Lemo beach area can become a cultural and natural tourism area. And the importance of maintaining environmental cleanliness, especially in the Tanah Lemo beach area.